SOME THOUGHTS ON WORLD-VIEWS AND EDUCATION - Malloy-Hanley, Erin (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1977)
One of the basic problems underlying the discussion of values and the future of education is the confusion caused by coexisting but divergent world-views. We could better appreciate the values perpetuated through the educational process if we come to terms with the world-views underlying what we value, how we value, and the manner in which we understand the very discussion of values. Everyone has a world-view or perspective on life. Not everyone, however, is aware of what this Weltanschauung is. As a result, we often send out conflicting signals about our own lives and are unable to understand the values of others who live in other countries, the house next door, or even in our own home. Only in the context of self and mutual understanding can communication about values become intelligible. There are at least three world-views underpinning communication today, views differing from each other in such a way that it is almost impossible for a person operating from within one world-view to appreciate and even, in some cases, to remain unthreatened by the behavior of someone operating from within a different one. Nevertheless, while people tend to live by a dominant world-view, most of us incorporate into our persons some combination of all three. The recognition and appreciation of the world-view(s) most operative in our lives and in the lives of others could facilitate the process of education today and develop respect for the diversity of education which seems inevitable tomorrow.